Characteristics of GPS, BDS2, BDS3 and Galileo inter-system biases and their influence on RTK positioning. (24th October 2019) - Mi, Xiaolong; Zhang, Baocheng; Yuan, Yunbin; Luo, Xiaowen
Abstract: The Chinese new-generation BeiDou navigation satellite system (BDS3) is under construction and has begun to provide satellite-based positioning, navigation and timing solutions for global users. Inter-system biases (ISBs) are critical for the optimal combination of multiple global navigation satellite systems (GNSSs) observations, and their calibration makes it possible to enhance the interoperability among different GNSSs. We formerly presented a method based on the between-receiver single-differenced (SD) multi-GNSS observation equations for estimating the ISBs in scenarios with both overlapping and non-overlapping frequencies. In this paper, we analyze the ISBs between the new-generation BDS3 and other GNSSs, as well as BDS2, using the previously proposed SD method. For the first time, this article presents the ISBs between BDS3 and GPS, Galileo and BDS2 for identical-receiver baselines. Numerical analysis indicates that (1) the new frequencies of BDS3 that overlap those of GPS and Galileo are, rather unexpectedly, free of ISBs, suggesting the existence of interoperability among these three constellations; (2) there are obvious ISBs between BDS3 and BDS2 at non-overlapping frequencies but not at overlapping frequencies; (3) calibrating the ISBs makes it possible to improve the performance of real-time kinematic (RTK) positioning for multiple GNSSs involving BDS3.